Malay Secondary School Students' Social Support Preferences: Implications for Support Network Interventions - Baba, Maznah (Universiti Putra Malaysia Press, 1993)
This exploratory study seeks to identify urban-Malay secondary school students' perceptions regarding the degrees of importance of twelve common social support (5S) types and six salient individual SS sources, in relation to an academic problem. The levels of importance/preference ascribed to the SS types and sources of SS were also examined for gender differences. 164 respondents (71 males and 93 females) volumarily participated in the study. Data were collected using a survey questionnaire. The twelve categories of SS were derived from Richard E. Pearson's (1986) Personal Support System Survey. Results showed that subjects' preferences with respect to SS for academic problems are multifaceted. They desire a combination of informational, emotional and appraisal supports from others. Subjects rated 'guidance' as the most important supportive response should they experience academic problems. Perceptions regarding the levels of importance attached to each SS type also differed between gender. Students perceived their parents as the most important source of SS. Of their parents, mothers were regarded as more important. The findings suggest that to help Malay students with academic problems, S5-focused interventions need to be multifaceted, teachers and counselors need training in collaborating with parents regarding their children's academic difficulties, parental support is more preferred than support from others, student-teacher communication needs improvement. Gender differences in SS type preferences need further examination.